The RNA cleavage activity of RNA polymerase III is mediated by an essential TFIIS-like subunit and is important for transcription termination - Chédin, Stéphane (Cold Spring Harbor Laboratory Press, 1998)
Budding yeast RNA polymerase III (Pol III) contains a small, essential subunit, named C11, that is conserved in humans and shows a strong homology to TFIIS. A mutant Pol III, heterocomplemented with Schizosaccharomyces pombe C11, was affected in transcription termination in vivo. A purified form of the enzyme (Pol III Δ), deprived of C11 subunit, initiated properly but ignored pause sites and was defective in termination. Remarkably, Pol III Δ lacked the intrinsic RNA cleavage activity of complete Pol III. In vitro reconstitution experiments demonstrated that Pol III RNA cleavage activity is mediated by C11. Mutagenesis in C11 of two conserved residues, which are critical for the TFIIS-dependent cleavage activity of Pol II, is lethal. Immunoelectron microscopy data suggested that C11 is localized on the mobile thumb-like stalk of the polymerase. We propose that C11 allows the enzyme to switch between an RNA elongation and RNA cleavage mode and that the essential role of the Pol III RNA cleavage activity is to remove the kinetic barriers to the termination process. The integration of TFIIS function into a specific Pol III subunit may stem from the opposite requirements of Pol III and Pol II in terms of transcript length and termination efficiency.